Fabrication and thermal analysis of epoxy resin-carbon fiber fabric composite plate-coil heat exchangers. (25th December 2017) - Viana, Silvia T.; Scariot, Vinicius K.; Provensi, Andre; Barra, Guilherme M.O.; Barbosa, Jader R.
Highlights: Carbon fiber fabric/epoxy resin heat exchangers were fabricated by compression/lamination. 1% wt. carbonaceous particle fillers were mixed in the epoxy resin to improve thermal conductivity. Thermal performance was evaluated based on infrared thermography and calorimetric measurements. Maximum overall surface efficiency and effective thermal conductivity were 0.86 and 6.5 W m −1  K −1. The impact of the 1% wt. carbonaceous particles on the overall thermal conductance was very small. Abstract: The fabrication and thermal performance assessment of plate-coil heat exchangers made from carbon fiber fabric and epoxy resin are presented and discussed. To increase the thermal performance of the heat exchanger material, the epoxy resin was mixed with 1% wt. carbonaceous particles, which resulted in a thermal conductivity enhancement of approximately 39% and 25% for graphene nanoplatelets and for expanded graphite mixtures, respectively. A direct assessment of the thermal performance of the polymer composite heat exchangers was carried out via infrared thermography to determine their overall surface efficiency and via calorimetric measurements in a purpose-built wind-tunnel to determine their overall thermal conductance. An overall surface efficiency of the order of 0.86 and an effective thermal conductivity in the range of 6.1–6.5 W m −1  K −1 have been found. Although the 1% wt. carbonaceous particle filling enhanced significantly the thermal conductivity of the epoxy resin, their overall contribution to the effective thermal conductivity of the carbon fiber fabric heat exchanger was found to be very small.